(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is devoted to the analysis of working-out the question of the asyndetic complex sentence in the Ukrainian and Russian linguistics, it is done a try to compare the aspects and the patterns of the research of the given topic. It is determined the tendencies of the further development of studying the asyndetic complex sentence.